The Fatty Acid Composition of Diacylglycerols Determines Local Signaling Patterns1. Issue 24 (29th May 2013) - Nadler, André; Reither, Gregor; Feng, Suihan; Stein, Frank; Reither, Sabine; Müller, Rainer; Schultz, Carsten
<x xml:space="preserve">Abstract</x> Caged compounds are designed to release biologically active signaling molecules with temporal, spatial, and even subcellular resolution. But how localized does the signal stay? Using the example of diacylglycerol, some signal responses (PKC) are shown to remain spatially distinct while other signals ([Ca2+]i) spread across the entire cell. Surprisingly, this distribution patterns depend on the fatty acid composition of the lipid species.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>